The Effect of Earning Per Share, Price to Book Value, and Price Earning Ratio on the Share Price of PT. Express Transindo Utama Tbk - Irawan, Adelia Dewi; Herlinawati , Erna; Herlina, Listri (International Journal of Finance Research, 2023)
This study aims to analyze the effect of earnings per Share (EPS), Price to Book Value (PBV), and Price Earning Ratio (PER) on the share price of PT Express Transindo Utama Tbk listed on the Indonesia Stock Exchange during the period 2012-2022. PT Express Transindo Utama Tbk is one of the leading transportation companies in Indonesia and has shares traded on the stock exchange. This study uses historical data of EPS, PBV, PER, and stock price of PT Express Transindo Utama Tbk during the specified research period. These data were then analyzed using multiple linear regression methods to identify the relationships between these variables. However, the study also revealed that external factors such as stock market conditions, macroeconomic situation, and government policies can also affect the share price of PT Express Transindo Utama Tbk during the study period. Fluctuations in crude oil prices and the global COVID-19 pandemic are some examples of external factors that affected the company's share price during the study period.